Identification of Key lncRNA–mRNA Pairs and Functional lncRNAs in Breast Cancer by Integrative Analysis of TCGA Data - Li, Zhe; Qian, Zheng; Chen, Fei; Jiang, Shujun; Meng, Lingjia; Chen, Jinzhong (Frontiers in Genetics, 2021)
Long non-coding RNAs (lncRNAs) play an important role in many diseases and are involved in the post-transcriptional regulatory network of tumours. The purpose of this study is to mine new lncRNA-mRNA regulatory pairs and analyse the new mechanism of lncRNA involvement in the breast cancer progression. Using breast cancer miRNA and mRNA expression profiling from The Cancer Genome Atlas (TCGA), we identified 59 differentially expressed lncRNAs, 88 differentially expressed miRNAs and 1465differentially expressed mRNAs. Whereafter, four candidate lncRNAs (FGF14-AS2, LINC01235, AC055854.1, and AC124798.1) were identified by Kaplan-Meier. Furthermore, we screened the hub lncRNAs (LINC01235) through univariate cox, multivariate cox analysis and qPCR validation, which was significantly correlated with breast cancer stage, ER status and pathological N. Subsequently, 107 LINC01235-related mRNAs were obtained by combining differentially expressed miRNAs, differentially expressed mRNAs, LINC01235 targeting miRNAs and mRNAs. The protein-protein interaction (PPI) network was established by Cytoscape software, and 53 key genes were screened. Function and pathway enrichment show that LINC01235 related key genes may be involved in the process of cell differentiation, proliferation and p53 signal pathway. In addition, in vitro experiments confirmed that LINC01235 can regulate the proliferation, migration and invasion of breast cancer cells. Furthermore, we screened three mRNAs (ESR1, ADRA2A and DTL) associated with breast cancer drug resistance from key genes. Through in vitro knockout experiments and correlation analysis, we found that there is a negative feedback mechanism between LIN1234 and ESR1, ADRA2A. In conclusion, our results suggest that LINC01235-ESR1 and LINC01235-ADRA2A could serve as important co-expression pairs in the progression of breast cancer, and LINC01235 plays a key role as an independent prognostic factor in patients with breast cancer. The findings of this work greatly increase our understanding of the molecular regulatory mechanisms of lncRNA in breast cancer.